2002
DOI: 10.1179/joc.2002.14.4.378
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Medical Therapy of Infections Following Osteosynthesis: a Retrospective Analysis of a Six-Year Experience

Abstract: The conventional therapeutic approach to bone infection associated with osteosynthesis is based on the idea that microbial eradication is most readily achieved by removal of the foreign material together with adequate antimicrobial therapy. This strategy usually requires implantation of external fixation devices with additional discomfort to the patient. We report our experience with conservative medical and antimicrobial therapy without removal of the osteosynthesis until adequate bone callus deposition is do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…In this patient, multimodal approach with stepwise reconstruction of the severely traumatized tissue and directed antibiotic therapy against E. faecium allowed recovery from this injury with a good functional result [3,5]. The basic principles of limb salvage using external fixation and control of the initial severe soft tissue injury using a VAC system and secondary stabilization and an attempt to treat the fractures with osteosynthesis were followed [7,8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this patient, multimodal approach with stepwise reconstruction of the severely traumatized tissue and directed antibiotic therapy against E. faecium allowed recovery from this injury with a good functional result [3,5]. The basic principles of limb salvage using external fixation and control of the initial severe soft tissue injury using a VAC system and secondary stabilization and an attempt to treat the fractures with osteosynthesis were followed [7,8].…”
Section: Discussionmentioning
confidence: 98%
“…In case of trauma with requirement of reconstruction using metallic implants also other pathogens may be involved depending on the initial contamination [2,3]. Control of contamination=infection prior to implantation is desirable; however, it cannot always be achieved and therefore, during surgery of open fractures, perioperative prophylaxis using broad-spectrum antibiotics is used.…”
mentioning
confidence: 99%
“…This strategy usually requires the implantation of external fixation devices with additional discomfort to the patient. Pavoni et al [201] reported their experience with 20 patients with infections associated with intramedullary nailing (9 patients) screws and plates (9 patients) or screw (2 patients) treated between 1995 and 2000. The offending pathogens were S. aureus (17 cases), S. aureus plus Escherichia coli and S. epidermidis (1 case each).…”
Section: Antibiotic Treatment Of Osteomyelitis With Implant Materialsmentioning
confidence: 98%
“…One example is ciprofloxacin, which is being indicated for several cases. [6][7][8][9][10][11][12][13] This is a bactericide antibiotics belonging to 2nd generation quinolones class, of which mechanism of action is to inhibit bacterial DNA synthesis by its cleavage. Its action is more effective when its serum concentration is thirty times higher than the minimum inhibitory concentration.…”
Section: Discussionmentioning
confidence: 99%